Interaction Between International Exchange Rate and Indonesian Finance Stock Index - Azis, Muh. Irfandy; Karunia, Erick (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
This suggests that while short-term fluctuations are inevitable, the exchange rates and stock market tend to realign over time. The Granger causality test uncovers bidirectional causality between the USD/IDR and EUR/IDR exchange rates and the financial index, indicating that not only do changes in exchange rates impact the stock index, but stock market performance also influences exchange rate movements. The impulse response function shows that shocks to the USD/IDR exchange rate have the most significant and lasting impact on the IDX Finance index, reflecting the dominant role of the US dollar in global trade and finance. The findings have important implications for policymakers and investors. Policymakers should focus on maintaining exchange rate stability, especially relative to the USD, to foster a stable investment environment and support long-term growth in the financial sector. For investors, exchange rate trends, particularly the USD/IDR, should be closely monitored, as these fluctuations significantly affect the financial sector's profitability and overall stock market performance. The study contributes to the broader literature by highlighting the complex interplay between exchange rates and financial markets in emerging economies